Unknown copies of the lost charters of Le Mont Saint-Michel (11th-13th C.). The Henry Chanteux collection at the Archives Départementales du Calvados - Allen, R (Brepols Publishers, 2018)
This article examines a previously unknown collection of material compiled in relation to the abbey of Le Mont Saint-Michel by the archivist and historian Henry Chanteux (1904-1995). Conserved today at the Archives départementales du Calvados in Caen, it includes transcripts of almost eighty of the abbey's charters, the uncatalogued and unlisted originals of which were destroyed during the Allied bombing of Normandy on 6 June 1944. The copies collected or made by Chanteux not only preserve for us texts that would otherwise be unknown, but help shed light on a range of wider issues, from the management of the abbey's estates to its efforts to attract pilgrims to its door. The article includes a complete listing of the acts preserved in the Chanteux collection, and an edition of a dossier of ten charters relating to the church of Argouges (Manche), which was a frequent source of dispute between Le Mont and the abbey of Marmoutier.